2013
DOI: 10.1371/journal.pone.0079866
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Genome-Wide Association Studies for Identifying Markers for Wood Property and Male Strobili Traits in Cryptomeria japonica

Abstract: Genome-wide association studies (GWAS) are an alternative to bi-parental QTL mapping in long-lived perennials. In the present study, we examined the potential of GWAS in conifers using 367 unrelated plus trees of Cryptomeria japonica D. Don, which is the most widely planted and commercially important tree species in Japan, and tried to detect significant associations between wood property traits and quantity of male strobili on the one hand, and 1,032 single nucleotide polymorphisms (SNPs) assigned to 1,032 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 100 publications
(120 reference statements)
2
41
0
Order By: Relevance
“…This consideration of relatedness considerably reduced p -value inflation, for both traits. Similar results were reported for wood quality and growth traits in Eucalyptus globulus [70, 71] and for wood property traits in Cryptomeria japonica [72]. Only seven of the 2,498 SNPs, from six different loci, were found to be significantly associated with the traits considered (p < 0.001).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This consideration of relatedness considerably reduced p -value inflation, for both traits. Similar results were reported for wood quality and growth traits in Eucalyptus globulus [70, 71] and for wood property traits in Cryptomeria japonica [72]. Only seven of the 2,498 SNPs, from six different loci, were found to be significantly associated with the traits considered (p < 0.001).…”
Section: Discussionsupporting
confidence: 82%
“…[16], with 20 SNPs from a set of 52 SNPs specifically selected from previous QTL and association mapping studies found to be associated with height. In general, the proportion of marker-trait associations detected for other quantitative traits, such as wood properties [72, 81, 82], adaptive traits [8385], and metabolite content [86], was slightly higher than that for growth traits. The strategy used (candidate gene-based vs. non-targeted approaches) and the genetic architecture of the traits therefore play a major role in the discovery of marker-trait associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMMA’s approach is powerful and has been used to analyze a variety of phenotypes in mice (Bennett et al 2010; Kirby et al 2010; Johnson et al 2012; Hersch et al 2012; Ghazalpour et al 2012; Courtney and Massett 2012; Himes et al 2013; Mott et al 2014) and other organisms (Uchiyama et al 2013; Rosas et al 2013). However, because EMMA also re-estimates variance components for each individual marker (Kang et al 2008), it is very slow when analyzing large, densely genotyped samples.…”
Section: Mixed Model Association Softwarementioning
confidence: 99%
“…As selected loci and SNPs are associated with a target trait, GWASs can be used for the development of useful molecular markers. Furthermore, by comparing previous QTL mapping and GWAS results, the orientation of a molecular marker can be proposed and applied to a marker‐assisted selection strategy to reduce apple breeding times and labour (Iwata et al., ; Uchiyama et al., ). Thus, high‐density genetic maps and various markers are needed for effective apple breeding, and various approaches such as QTL mapping and GWAS are performed for many plants.…”
Section: Introductionmentioning
confidence: 99%